Observations of the South Atlantic Subtropical Mode Water using PIES data - Cortezi, Matheus Vasconcellos (2017)
Subtropical mode water is a voluminous body of water in the ocean whose main feature is the homogeneity in both vertical structure and horizontal extension. The subtropical mode water (STMW) of the southwest Atlantic is formed between the months of July and October near the Brazil-Malvinas confluence and along the Brazil Current recirculation gyre. The formation region extends on the order of 3000 km zonally, from 20°W to 50°W, and 1000 km meridionally, from 30°S to 40°S, and it is typically about 170 m thick. In situ data from pressure-equipped inverted echo sounders (PIES) installed in the western portion of the basin, along 34.5°S, are available from 2009 to the present. These data after processed and calibrated can provide an unprecedented description of the STMW involving processes since its formation at the surface until the final stage of its residence in the interior of the ocean. Temperature and salinity data estimated by the PIES are based on empirical look-up tables that relate the acoustic travel time with the baroclinic structure of the ocean. This technique is known as the Gravest Empirical Mode (GEM), and here it is used to detect profiles containing homogeneous segments of temperature and salinity that characterize the mode water. The GEM method was seasonally corrected to reconstruct surface variability necessary for STMW formation. The interannual covariance between STMW layer thickness and the Brazil Current was calculated, but no significant correlation at that time scale was observed. The mode water layer detected was about 220 m ± 55 m thick on all sites, agreeing with previous studies.